Auditing students' perceptions of online assessments and e-proctoring systems - E. A. J. Terblanche; Annelien Adriana van Rooyen; P. C. Enwereji (Springer, 2024)
Abstract The COVID-19 pandemic accelerated the implementation of online assessments at an unprecedented pace. The pandemic required most higher education institutions worldwide to implement online assessments almost overnight. The study aimed to gain an understanding of auditing students' perceptions of online assessments and e-proctoring systems during the pandemic. A web-based questionnaire was administered to postgraduate auditing students who had taken part in remote online assessments at an open distance and e-learning university in South Africa, invigilated via e-proctoring software, which was introduced in the 2020 academic year. A total of 238 students participated in the study. Factor analysis, using principal component factor analysis, was performed to identify the factors or components that possibly caused the variation in these auditing students' perceptions of online assessments and e-proctoring. Varimax with Kaiser normalisation was used as a rotation method. This process revealed five main components that explained variations in participants' perceptions, namely: Component 1-emotions (assessments), appropriateness (assessments), fairness (assessments), monetary aspects, and time; Component 2-practical IT matters, academic integrity (e-proctoring) and cheating (e-proctoring); Component 3-practical IT matters (e-proctoring) and emotions (e-proctoring); Component 4-practical IT matters (assessments) and time (assessments); and Component 5-cheating (assessments). Implications of the findings for educators are offered, along with recommendations for future research.